A Review of 52 Pedigrees with Epidermolysis Bullosa Simplex Identifying Ten Novel Mutations in KRT5 and KRT14 in Australia - Emma N. Kim; Adam G. Harris; Linda J. Bingham; Wenfei Yan; John C. Su; Dedee F. Murrell (Medical Journals Sweden, 2017)
Epidermolysis bullosa simplex (EBS) is a rare heritable skin fragility disorder, most commonly caused by dominant mutations in KRT5 and KRT14. EBS shows clinical heterogeneity with localised, intermediate and generalised severe forms, which tend to correlate with the location and nature of the disease causing mutations. We therefore aimed to identify the KRT5 and KRT14 mutations in patients diagnosed with EBS in Australia, and explore in depth the genotype to the phenotype correlations in patients with novel variants. Australian patients who were diagnosed with EBS after referral to the Australian National Diagnostic Laboratory for EB were offered mutation screening in the KRT5 and KRT14 genes. From this, 32 different mutations in KRT5 and KRT14 were identified within 39 of 52 pedigrees. Ten of these mutations from 9 different pedigrees were novel, a further fatal case caused by KRT5 E477K is reported and in addition the third reported case of digenic inheritance in EBS was also observed.